Creative Problem Solving-Based Electronic Module Integrated with 21st Century Skills - Widya, Widya; Maielfi, Dini; Alfiyandri, Alfiyandri; Hamidah, Wanda (Indonesian Journal of Science and Mathematics Education, 2021)
Teachers as facilitators in learning are expected to develop learning that integrates 21st-century skills so that students are ready to compete in this era. One of the things teachers can do is develop e-modules based on the Creative Problem Solving (CPS) model. This research is research and development with 4D models. The purpose of this study is to produce an integrated 21st-century physics e-module based on the CPS model. Data analysis using descriptive analysis. Research results: E-module physics based on CPS model integrated 21st-century skills have met the valid criteria: for the content, feasibility component is in the very valid category with a value of 93.18, the presentation component is in the very valid category with a value of 85, the graphic component is in the category very valid with a value of 95.45, and the language component is in the very valid category with a value of 83. Therefore, this CPS-based e-module has met the criteria to be piloted in schools.